Impact of the test and treat policy on delays in antiretroviral therapy initiation among adult HIV positive patients from six clinics in Johannesburg, South Africa: results from a prospective cohort study. Issue 3 (25th March 2020) - Onoya, Dorina; Sineke, Tembeka; Hendrickson, Cheryl; Mokhele, Idah; Maskew, Mhairi; Long, Lawrence C; Fox, Matthew
Abstract : Objectives: To assess delays to antiretroviral therapy (ART) initiation before and after the Universal Test and Treat (UTT) and the same-day initiation (SDI) of ART policy periods in Johannesburg, South Africa. Design: Prospective cohort study. Setting: Patients were recruited from six primary health clinics in Johannesburg. Participants: Overall, 1029 newly diagnosed HIV positive adults (≥18 years) were consecutively enrolled by referral from the testing counsellor between April and December 2015 (pre-UTT n=146), July and August 2017 (UTT, n=141) and October 2017 and August 2018 (SDI, n=742). Main outcome measures: Cox proportional hazards regression was used to assess predictors of 30 days ART initiation. Additionally, predictors of immediate ART initiation were evaluated using Poisson regression. Results: Overall, 30 days ART proportions were 71.9% overall, 36.9% pre-UTT (44.3% of those eligible), 65.9% under UTT and 79.9% under the SDI policy. The median days to ART initiation declined from 21 pre-UTT (IQR: 15–30) to 8 (IQR: 6–16) under UTT and 5 days (IQR: 0–8) under the SDI policy. However, only 150 (20.2%) of the SDI cohort-initiated ART immediately after HIV diagnosis. Living in a two-adult home (adjusted HR (aHR) 1.2 vs living alone, 95% CI 1.0 to 1.5) increased the likelihood of 30-day ART. Missing baseline cluster of differentiation four (CD4) data decreased the likelihood of 30 days ART by 40% (aHR 0.6 vs CD4 <350 cells/µL, 95% CI 0.5 to 0.7). More women took up immediate ART (adjusted relative risk (aRR) 1.3, 95% CI 1.0 to 1.9). Participants ≥40 years (aRR 0.6 vs 18–24 years, 95% CI 0.4 to 0.9) were less likely to start ART immediately after HIV diagnosis. However, immediate ART rates increased with longer policy implementation time (aRR 0.2 for <3 months vs >10 months, 95% CI 0.1 to 0.4). Conclusions: The study results highlight a positive move towards earlier ART initiation during the UTT and SDI periods and emphasise a need to increase same-day ART implementation further.